Population delimitation in bumble bees - strategies and research gaps - Gornall, Lilian; Dauber, Jens; Sickel, Wiebke (Frontiers in Bee Science, 2025)
Declining social insects such as bumble bees are particularly vulnerable to loss of genetic diversity. Population delimitation is a precondition for measuring genetic diversity but usually requires extensive genetic data and comprehensive knowledge about gene flow barriers. As a first step towards a delimitation strategy that does not rely on genetic data, we compiled existing knowledge about Bombus population structures and (potential) gene flow barriers. We reviewed studies examining genetic structuring in Bombus species and assessed the impact of different ecological and environmental factors on their gene flow. Generally, we found that declining species and clearly isolated populations exhibit genetic structuring for which some underlying factors can be correlated with isolation-by-landscape approaches. For widespread species, isolation-by-environment approaches can help elucidate subtle factors impeding gene flow between populations, even though such species are capable of maintaining gene flow across large stepping stone populations. However, to better inform isolation-by landscape/environment models that could contribute to a landscape-based population delimitation strategy, more research into habitat requirements and dispersal ranges has to be conducted.